Precipitation‐drainage cycles lead to hot moments in soil carbon dioxide dynamics in a Neotropical wet forest. (10th July 2020) - Fernandez‐Bou, Angel Santiago; Dierick, Diego; Allen, Michael F.; Harmon, Thomas C.
Abstract: Soil CO2 concentrations and emissions from tropical forests are modulated seasonally by precipitation. However, subseasonal responses to meteorological events (e.g., storms, drought) are less well known. Here, we present the effects of meteorological variability on short‐term (hours to months) dynamics of soil CO2 concentrations and emissions in a Neotropical wet forest. We continuously monitored soil temperature, moisture, and CO2 for a three‐year period (2015–2017), encompassing normal conditions, floods, a dry El Niño period, and a hurricane. We used a coupled model (Hydrus‐1D) for soil water propagation, heat transfer, and diffusive gas transport to explain observed soil moisture, soil temperature, and soil CO2 concentration responses to meteorology, and we estimated soil CO2 efflux with a gradient‐flux model. Then, we predicted changes in soil CO2 concentrations and emissions under different warming climate change scenarios. Observed short‐term (hourly to daily) soil CO2 concentration responded more to precipitation than to other meteorological variables (including lower pressure during the hurricane). Observed soil CO2 failed to exhibit diel patterns (associated with diel temperature fluctuations in drier climates), except during the drier El Niño period. Climate change scenarios showed enhanced soil CO2 due to warmer conditions, while precipitation played a critical role in moderating the balance between concentrations and emissions. The scenario with increased precipitation (based on a regional model projection) led to increases of +11% in soil CO2 concentrations and +4% in soil CO2 emissions. The scenario with decreased precipitation (based on global circulation model projections) resulted in increases of +4% in soil CO2 concentrations and +18% in soil CO2 emissions, and presented more prominent hot moments in soil CO2 outgassing. These findings suggest that soil CO2 will increase under warmer climate in tropical wet forests, and precipitation patterns will define the intensity of CO2 outgassing hot moments. Abstract : Tropical wet forests are essential to preserve the global carbon balance, yet tropical soil‐carbon dynamics are not well understood. We study the short‐term effects of meteorological variability and predict the long‐term effects of climate change on soil CO2 in a Neotropical wet forest in Costa Rica. Short‐term soil CO2 emissions include significant out‐gassing events ("hot moments") which were associated with rainfall events. Simulated long‐term warming scenarios resulted in increased soil CO2 concentrations, with drier future conditions increasing emissions the most. Our findings suggest that tropical wet forest soil CO2 will increase under climate change while precipitation patterns will regulate emissions.